The potential of SiK® fertilization in the resilience of chestnut plants to drought - a biochemical study - Carneiro-Carvalho, Andreia; Pinto, Teresa; Gomes-Laranjo, José; Anjos, Rosário (Frontiers in Plant Science, 2023)
Silicon, being an essential mineral nutrient, plays a crucial role in the metabolic, biochemical, and functional mechanisms of many crops under environmental stress. In the current study, we evaluated the effect of SiK® fertilization on the biochemical defense response in plants exposed to water stress. Castanea sativa plants were exogenously fertilized with different concentrations of potassium silicate (0 mM, 5mM, 7.5 mM, and 10 mM SiK®) and exposed to a non-irrigation phase and an irrigation phase. The results indicate that silicon promoted the synthesis of soluble proteins, decreased the proline content and the oxidative stress (reduced electrolyte leakage, lipid peroxidation, and hydrogen peroxide accumulation) in tissues, due to an increase in ascorbate peroxidase, catalase and peroxidase activity, which was accompanied by the rise in total phenol compounds and the number of thiols under drought conditions. This study suggests that exogenous Si applications have a protective role in chestnut plants under water deficit by increasing their tolerance to this abiotic stress.